Changes in electromechanical delay during fatiguing dynamic muscle actions. Issue 2 (6th April 2017) - Smith, Cory M.; Housh, Terry J.; Hill, Ethan C.; Johnson, Glen O.; Schmidt, Richard J.
ABSTRACT: Introduction: The onsets of the electromyographic (EMG) signal, mechanomyographic (MMG) signal, and force production were used to identify voluntary electromechanical delay (EMD) during maximal and submaximal leg extensions. Methods: Twelve men performed 30% 1‐repetition‐maximum concentric, dynamic constant external resistance leg extensions to failure. The time periods for the onsets of EMG to MMG (EMDE‐M ), MMG to force (EMDM‐F ), and EMG to force (EMDE‐F ) were assessed before, during, and after testing. Results: Pretest vs. posttest assessments indicated approximately equal contributions from excitation–contraction coupling (EMDE‐M ) and series elastic component (EMDM‐F ) to the overall EMDE‐F . During the workbout, excitation–contraction coupling failure and increases in the compliance of the series elastic component began at 40% and 30% of the repetitions to failure, respectively, and continued to failure. Conclusions: Increases in the series elastic component (EMDM‐F ) began to affect EMDE‐F before excitation–contraction coupling failure (EMDE‐M ), and both contributed to EMDE‐F throughout the remainder of the fatiguing workbout. Muscle Nerve 56 : 315–320, 2017